Monotonic and cyclic response of speed-lock connections with bolts in storage racks. (1st June 2016) - Yin, Lingfeng; Tang, Gan; Zhang, Min; Wang, Bingjing; Feng, Bo
Highlights: Proposed several new connections by adding bolts or/and welding to traditional speed-lock connections. Investigated the failure modes of new connections in detail through monotonic and cyclic experiments. Studied the stiffness and hysteretic responses of all connections. Explored the energy dissipation capabilities from the hysteretic responses for all the connections. Investigated the ductility and stiffness degradation of all the connections. Abstract: The purpose of this paper is to explore the bearing capacity and energy dissipation of several variations of speed-lock connections of cold-formed steel storage racks. Commonly used speed-lock connection exists large slippage and low energy dissipation capacity, new speed-lock connections with additional bolts (and welds) are investigated in order to enhance its performance. Their monotonic behavior and hysteretic response under cyclic loading were studied experimentally using a cantilever test method. The tests were conducted using both the EN 15512 monotonic protocol and AISC seismic provisions' cyclic-test protocol for each specimen. The failure modes, moment–rotation response, and associated stiffnesses, bearing capacities, and energy dissipation capabilities were fully investigated. Both monotonic and cyclic responses showed that the additional bolts (and welds) significantly enhanced the bearing capacities and deformability of the connections, though the initial stiffness and equivalent stiffness (i.e., according to the EN 15512 specification) showed little improvement. The hysteretic responses of all connection variations investigated demonstrated pinching behaviors. The energy dissipation capability has been greatly improved with additional bolts (and welds) except of the one with only lower bolts, which could also be corroborated through the analyses of the calculated equivalent viscous damping coefficient and the displacement ductility factor. In addition, the stiffness degradation has been observed for both positive loading and negative loading, and adding bolts and welds could effectively reduce this effect.